Pain, Depression, and Health-Related Quality of Life of Older Haenyeos (Women Divers) - Eun Suk Ko; Kyung-Ja Kang (JMIR Publications, 2018)
This study aimed to provide basic data in order to develop effective intervention plans to improve the health-related quality of life of older haenyeos (professional female free divers). The study's participants consisted of older haenyeos (≥65 years old) from seven fishing villages on Jeju Island, Korea. Data were collected using a questionnaire-based survey method, and the responses of 149 participants were analyzed. The participants' mean pain score was 2.43 out of 5 points and their mean score for health-related quality of life was 61.18 out of 100 points. Depression was the strongest factor influencing health-related quality of life; other influencing factors included pain, the number of drug side effects, number of drugs prescribed, age, and diving time. Intervention plans for chronic-disease management and self-management programs tailored to the characteristics of older haenyeos are needed for the effective control of depression, pain, and improvement in their health-related quality of life.